2019
DOI: 10.1186/s12967-019-1998-9
|View full text |Cite
|
Sign up to set email alerts
|

The epigenome as a putative target for skin repair: the HDAC inhibitor Trichostatin A modulates myeloid progenitor plasticity and behavior and improves wound healing

Abstract: Background The molecular pathways that drive bone marrow myeloid progenitors (BMMP) development are very well understood and include a tight controlled multi-stage gene hierarch. Monocytes are versatile cells that display remarkable plasticity and may give rise to specific subsets of macrophages to proper promote tissue homesostasis upon an injury. However, the epigenetic mechanisms that underlie monocyte differentiation into the pro-inflammatory Ly6C high or the repairi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…We showed that in the absence of HDAC activity the number of LURP-GFP + cells in the regenerative bud was increased without a consistent increase in the levels of endogenous mRNA levels of LURP. Interpreting this result, we found a stinking similar pattern observed in mice upon iHDAC treatment of myeloid precursors at 24 hpa (Cabanel et al, 2015; Cabanel et al, 2019). While control group displayed a lower number of LURP-GFP+ cells, these cells might express high levels of this protein being classified as LURP-GFP high sub-set (pro-inflammatory monocytes).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We showed that in the absence of HDAC activity the number of LURP-GFP + cells in the regenerative bud was increased without a consistent increase in the levels of endogenous mRNA levels of LURP. Interpreting this result, we found a stinking similar pattern observed in mice upon iHDAC treatment of myeloid precursors at 24 hpa (Cabanel et al, 2015; Cabanel et al, 2019). While control group displayed a lower number of LURP-GFP+ cells, these cells might express high levels of this protein being classified as LURP-GFP high sub-set (pro-inflammatory monocytes).…”
Section: Discussionsupporting
confidence: 80%
“…In this work we showed that the treatment of regenerating swimming tadpoles, starting at stage 40, with HDAC inhibitors (iHDACs) impairs regeneration and leads to a lack of regenerative ability. In addition, we have recently shown that iHDAC treatment of mammalian myeloid cells both in vitro and in vivo disrupts myeloid differentiation favoring cell cycling in detriment of cell differentiation (Cabanel et al, 2015; Cabanel, da Costa, El-Cheikh, & Carneiro, 2019). As a consequence, myeloid progenitors display a high plastic phenotype favoring an anti-inflammatory functional profile.…”
Section: Introductionmentioning
confidence: 99%
“…Upon differentiation, HDACs further promote the M1 phenotype, while class I-IIa HDAC inhibitor trichostatin A promotes elongated shape and potential to transition into a M2 phenotype through chromatin changes specifically involving H4K16. 127,128 Trichostatin A topically added to murine wounds mirrored the behaviour observed in vitro resulting in enhanced wound closure. 128 Class I HDACs downregulate myeloid plasticity and favour differentiation into "pro-inflammatory" M1 macrophages, while inhibition renews macrophage plasticity.…”
Section: Histone Modifications In Macrophagesmentioning
confidence: 80%
“…128 Class I HDACs downregulate myeloid plasticity and favour differentiation into "pro-inflammatory" M1 macrophages, while inhibition renews macrophage plasticity. 128 But HDACs do not all have the same function, even within the same class, as gene profiling of peripheral blood monocytes (PBMCs) in patients with type 2 DM and DFUs demonstrated differential regulation of HDACs in the context of increased pro-inflammatory mediators. 129,130 Among DFU patients, significant upregulation of class I HDACs 1,…”
Section: Histone Modifications In Macrophagesmentioning
confidence: 99%
“…This differential regulation may be useful if specific HDACs and downstream pathways can be targeted during healing. For example, TSA, which is HDAC class I‐IIa specific accelerates skin closure and enhances monocyte and macrophage populations in the wound bed, 95 while Sirtinol (class III HDAC inhibitor) slows healing 96 . Thus, specific blockade of HDAC III accelerates keratinocyte proliferation and enhances growth factor transcription, including IGF‐1, FGF, and EGF 96 …”
Section: Micrornasmentioning
confidence: 99%